2019
DOI: 10.1177/2473011419868971
|View full text |Cite
|
Sign up to set email alerts
|

Complications and Early Radiographic Outcomes of Flatfoot Deformity Correction With Metallic Midfoot Opening Wedge Implants

Abstract: Background: Forefoot varus is a common component of flatfoot deformity that is often surgically addressed. Multiple options exist to plantarflex the medial column, with midfoot fusion and the Cotton osteotomy being the most common. This study analyzes radiographic outcomes and complications when a titanium wedge is used for structural support in a dorsal opening wedge Cotton osteotomy of the medial cuneiform. Methods: Between December 2016 and May 2018, 32 feet in 31 patients were treated with medial column ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Encouragingly, the angles were shown to be comparable to the post-operative values otherwise obtained in joint-preserving procedures in young adults [16]. The talo-first metatarsal angle on lateral view, the so-called Meary's angle, represents one of the most important radiological criteria regarding the assessment of flatfoot deformity.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Encouragingly, the angles were shown to be comparable to the post-operative values otherwise obtained in joint-preserving procedures in young adults [16]. The talo-first metatarsal angle on lateral view, the so-called Meary's angle, represents one of the most important radiological criteria regarding the assessment of flatfoot deformity.…”
Section: Discussionsupporting
confidence: 59%
“…When this study was planned, reviews of other studies focusing on a similar question revealed a comparable number of patients [10,[16][17][18][19]. Statistical analyses were performed using SPSS v. 23 software (IBM Dtl.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 11 articles met the eligibility criteria for inclusion in this systematic review from 113 articles initially retrieved from the five databases [11][12][13][14][15][16][17][18][19][20][21]. All 11 articles were initially found on the five databases and no additional articles were included from further reference searches of the included articles.…”
Section: Search Resultsmentioning
confidence: 99%
“…For patients with both preoperative and postoperative measurements, patients (n = 88, 19.8% of patients) who received metallic wedges had a frequency-weighted mean preoperative lateral calcaneal pitch angle of 13.6 ± 0.6 degrees and a frequency-weighted mean postoperative lateral calcaneal pitch angle of 19.2 ± 1.6 degrees, whereas patients (n = 27; 6.1% of patients) who received bone allograft wedges had a mean preoperative lateral calcaneal pitch angle of 12.9 degrees and a postoperative lateral calcaneal pitch angle of 25.4 degrees [13]. Furthermore, Fraser et al ( 2019) reported an improvement of 3.1 degrees in patients who received metallic wedges during operative correction of PCFD deformity (n = 31) [13]. For patients with preoperative and postoperative measurements of Meary's angle, patients (n = 139; 31.3% of patients) who received metallic wedges had a frequency-weighted mean preoperative angle of 2.3 ± 15.5 degrees and a frequency-weighted mean postoperative angle of 2.2 ± 4.8 degrees, whereas patients (n = 18; 4.1% of patients) who received bone allograft wedges had a mean preoperative angle of 9.8 degrees and a mean postoperative angle of 1.8 degrees.…”
Section: Radiographic Outcomes After Wedge Utilizationmentioning
confidence: 99%
See 1 more Smart Citation